Novel sensitive monoclonal antibody based competitive enzyme-linked immunosorbent assay for the detection of raw and processed bovine beta-casein - Castillo, Daniela Susana (2017)
Cow milk protein allergy (CMPA) is the most common childhood food allergy, which can sometimes persist or can newly develop in adulthood with severe symptoms. CMPA’s treatment is complete dietary avoidance of milk proteins. To achieve this task, patients have to be aware of milk proteins found as "hidden allergens" in food commodities. In regard to milk proteins, it has been reported that allergenicity of caseins remains unaffected upon heat treatment. For these reasons, we aimed to obtain monoclonal antibodies (mAbs) against native and denatured β-casein, one of the most abundant and antigenic caseins, in order to develop an indirect competitive ELISA (icELISA) to detect and quantify traces of this milk allergen in raw and processed foodstuffs. We developed two specific hybridoma clones, 1H3 and 6A12, which recognized β-casein in its denatured and native conformations by indirect ELISA (iELISA). Cross-reaction analysis by Western blot and iELISA indicated that these mAbs specifically recognized β-casein from bovine and goat milk extracts, while they did not cross-react with proteins present in other food matrixes. These highly specific mAbs enabled the development of sensitive, reliable and reproducible icELISAs to detect and quantify this milk protein allergen in food commodities. The extraction of β-casein from foodstuff was efficiently carried out at 60C for 15 minutes, using an extraction buffer containing 1% SDS. The present study establishes a valid 1H3 based-icELISA, which allows the detection and quantification -0.29 ppm and 0.80 ppm, respectively- of small amounts of β-casein in raw and processed foods. Furthermore, we were able to detect milk contamination in incurred food samples with the same sensitivity as a commercial sandwich ELISA thus showing that this icELISA constitutes a reliable analytical method for control strategies in food industry and allergy prevention.